Differences in the Level life satisfaction in the Light of variables: Gender, specialization, and Level of Study - Ahmed Zegaoua (Social Empowerment Journal, 2021)
The study aimed to identify differences in life satisfaction among students of Ahmed Zabana University (Algeria). According to the variables of gender, academic specialization and level study. The sample of the study reached (140) students enabled by the Institute of Humanities and Social Sciences and the Institute of Science and Technology. The researcher used the descriptive approach in data processing and applied the life satisfaction scale designed by (Diener & al, 1985).  Students showed a level of life satisfaction with a mean score of (3.03) with a standard deviation of (SD=0.68). The most prevalent group was "satisfied" by (48%), followed by the "somewhat satisfied" group with (41.42%). The study revealed that there were no statistically significant differences attributed to the variable of gender and academic specialization, while there were significant differences attributed to the level study in favor of third-year graduating students.